Learning to reason: The influence of instruction, prompts and scaffolding, metacognitive knowledge, and general intelligence on informal reasoning about everyday social and political issues - David Perkins (Judgment and Decision Making, 2019)
Twelve experiments examined ways of improving informal reasoning, as assesed by presenting students with accessible, current, and interesting social and political issues, eliciting reasoning about them, and scoring the reasoning for quality of argument. The experiments asked: (1) the impact of established instructional programs that emphasized critical thinking (Experiments 1--4); (2) the impact of an investigator-designed high school level minicourse (Experiments 5--7); (3) the responsiveness of subjects to prompts that asked them to develop arguments more fully, and the relation of their responses to general intelligence (Experiments 8--10); (4) checks on the validity of the testing methodology (Experiments 11--12). Two of the established instructional programs had a beneficial effect. The minicourse had a particularly large effect on students' attention to the other side of the case, the most neglected aspect of informal reasoning. The prompting studies showed that subjects could develop their arguments far more than they normally did. Finally, subjects with higher intelligence were actually somewhat more biased in their reasoning. In summary: people can reason much better than they typically do on the sorts of issues posed; people are not performing near the limits of their abilities; strategies and standards of good reasoning can improve reasoning; and education can develop students' reasoning much further than education typically does.